Social organization: The thermodynamic basis - Bejan, A.; Gunes, U.; Errera, M. R.; Sahin, B. (WILEY, 2018)
Why do individuals come to live (to move) together, to organize? Here, we propose that organization is a reflection of the physics reality (bio and nonbio) that it takes less power (useful energy, fuel, food, and exergy) to move 1 unit of mass in bulk than to move 1 unit individually. The objective of this work is to establish the connection between energy engineering and social organization and to bring social organization under the big tent of physics. We illustrate the predictability of organization and its evolution with 2 simple models of movement on an area, one inanimate (river basins, generated by several rules of construction) and the other animate (distribution of heated water for use in human settlements). The 2 models lead to the same conclusion: The movement becomes more hierarchical as the size and complexity of the architecture increase. The distribution can be made more uniform (more equal) by imposing identical channels distributed uniformly over the area. The flow architecture becomes a grid instead of a tree; yet, even in designs with imposed equality, the hierarchy persists. This theoretical framework also reveals the physical meaning of innovation: It is a local design change that liberates the flow over the entire territory inhabited by the organized movers.
Keywords: constructal; economies of scale; evolution; hierarchy; innovation; organization; wealth; inequality; CONSTRUCTAL LAW; PHYSICS; LORENTE; DESIGN; BEJAN; Energy & Fuels; Nuclear Science & Technology